2011
DOI: 10.1088/0031-8949/2011/t145/014039
|View full text |Cite
|
Sign up to set email alerts
|

Sub-surface structures of ITER-grade W (Japan) and re-crystallized W after ITER-similar low-energy and high-flux D plasma loadings

Abstract: Abstract:Tungsten is a promising candidate for plasma facing materials in fusion reactors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 24 publications
(34 reference statements)
1
45
0
2
Order By: Relevance
“…This might be an explanation for the decrease in the low-temperature peak by annealing. On the other hand, vacancies can be generated by the high-flux plasma exposure as a result of plastic deformation due to high mechanical stresses created by the deuterium concentration strongly exceeding the solubility limit [12,15,16]. Dislocations themselves are probably too weak traps to retain deuterium at room temperature, as was discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…This might be an explanation for the decrease in the low-temperature peak by annealing. On the other hand, vacancies can be generated by the high-flux plasma exposure as a result of plastic deformation due to high mechanical stresses created by the deuterium concentration strongly exceeding the solubility limit [12,15,16]. Dislocations themselves are probably too weak traps to retain deuterium at room temperature, as was discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…It is pertinent to remind that intrinsic intergranular cracks ( temperatures below 500 K, the D retention in the ITER-grade W is higher than that for recrystallized W a) [9,15,21] (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Near room temperature, i.e. below BDTT, the stress relaxation results in brittle crack formation inside the grains [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…Typically blisters due to D implantation into W occur in this depth range [8,15,20]. It was recently suggested that blisters do not only retain D in form of molecules inside the cavity, but also D atoms in trap sites in the surrounding of the blisters which are created by plastic deformation of the W lattice [8].…”
mentioning
confidence: 99%